Switzerland : Financial Sector Assessment Program; Technical Note- Financial Safety Net and Crisis Management Arrangements. (IMF Staff Country Reports; Country Report, 2019)
Financial Sector Assessment Program; Technical Note- Financial Safety Net and Crisis Management Arrangements.